Ukraine's Patronal Democracy and the Russian Invasion The Russia-Ukraine War, Volume One - Madlovics, Bálint; Magyar, Bálint (Central European University Press, 2023)
The Russian invasion of Ukraine in 2022 jeopardizes the country's independence and its chances for Western-style development. However, the heroic attitude of the Ukrainian people, combined with a solidifying national identity, makes the domestic foundations for a western turn stronger than ever. After the invasion, building strong foundations of liberal democracy will be a top priority. In addition to alleviating immediate problems, the country must also address its post-communist legacy and address the constraints of patronalism. The authors of this edited volume, leading Ukrainian scholars supplemented by colleagues from Hungary, examine the chances of an anti-patronal transformation after the war. The book provides an overview of the development of Ukraine's political-economic system: color revolutions in 2004 and 2014 brought democratic transformation, but no change in the patronage system The result was patronal regime cycles instead of the emergence of a Western-type liberal democracy in the country. Building on the conceptual framework of the editors' The Anatomy of Post-Communist Regimes (CEU Press, 2020), the 12 chapters examine the impact of the war on patronal democracy, the relational economy, clientelist society, and the international environment in which Ukraine operates. This collection is complemented by the book entitled Russia. Imperial Endeavor and Geopolitical Consequences.